2008
DOI: 10.1111/j.1463-1326.2008.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of insulin glargine therapy in type 2 diabetes subjects suboptimally controlled on oral antidiabetic agents: results from the AT.LANTUS trial*

Abstract: Running title: Glargine initiation in insulin-naïve type 2 diabetes AT.LANTUS: A Trial comparing LANTUS Algorithms to achieve Normal blood glucose Targets in subjects with Uncontrolled blood Sugar 2 ABSTRACT Objective: For many patients with type 2 diabetes, oral antidiabetic agents (OADs) do not provide optimal glycemic control, necessitating insulin therapy. Fear of hypoglycemia is a major barrier to initiating insulin therapy. The AT.LANTUS study investigated optimal methods to initiate and maintain insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 39 publications
2
52
1
1
Order By: Relevance
“…Previous studies (10)(11)(12)(13)(14) have demonstrated improved glycaemic control after premixed insulin/insulin analogue Table II. Comparison of main efficacy indices prior to and after switch in the selected patients (± standard deviation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (10)(11)(12)(13)(14) have demonstrated improved glycaemic control after premixed insulin/insulin analogue Table II. Comparison of main efficacy indices prior to and after switch in the selected patients (± standard deviation).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated such novel treatment strategies (10)(11)(12)(13)(14) by adopting a two-back-one strategy, where premixed insulin/insulin analogues that were ineffective in patients with T2DM were replaced with insulin glargine plus OADs. Improved glycaemic control was observed in the patients following the switch in regimen.…”
Section: Introductionmentioning
confidence: 99%
“…If an individual perceives their illness to be easily understood, they may be more likely to adapt their behaviors based on their own knowledge of the illness. One study identified that in their sample of individuals newly diagnosed with T2DM, 33% admitted that they did not understand diabetes and 73% were unclear about which symptoms might relate to diabetes or other health concerns (Davies, Lavalle-Gonzalez, Storms, & Gomis, 2008). If an illness is seen as confusing, the individual may feel apprehensive in instances requiring decision-making and experience affective distress or low self-efficacy.…”
Section: Controllabilitymentioning
confidence: 99%
“…Research has supported the IPQ-R as having acceptable to excellent reliability 2011), and it has been used to measure change in illness perceptions in previous diabetes research trials (Davies et al, 2008;Skinner et al, 2011).…”
Section: Illness Representationmentioning
confidence: 99%
See 1 more Smart Citation